Small Intestinal Submucosa as an Intra-Articular Ligamentous Graft Material: A Pilot Study in Dogs - Aiken, S. W.; Badylak, S. F.; Toombs, J. P.; Shelbourne, K. D.; Hiles, M. C.; Lantz, G. C.; Van Sickle, D. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
This pilot study was performed to determine the potential for using small intestinal submucosa (SIS) xenografts for intra-articular ligament reconstruction. Porcine SIS was used to replace the excised cranial cruciate ligament (CCL) in five normal dogs. Grafts were evaluated histologically at 10, 12, 16, and 26 weeks after implantation. Two grafts were evaluated biomechanically at 26 weeks. All of the SIS neoligaments appeared macroscopically as white fibrous bands. The histological appearance progressed, with time, from disorganized immature connective tissue to large bundles of organized connective tissue, covered by a synovial membrane, that resembled the native CCL. There was no histological evidence of immune-mediated nor any foreign body reaction to the xenogeneic SIS graft material. The neoligaments 26 weeks after implantation had a maximum force to failure that was 16.2 and 21.4 times greater than the original SIS graft material and were 7.6 and 11.1 percent as strong as the contralateral control CCLs. We conclude that porcine SIS, used as an intra-articular graft material to replace the normal CCL in dogs, supported host tissue ingrowth, remodelled to form a ligamentous structure, and is worthy of further investigation.Small intestinal submucosa was used to replace the excised cranial cruciate ligament (CCL) in five normal dogs. The histo-logical appearance of the grafts progressively changed, with time, from disorganized immature connective tissue to large bundles of organized connective tissue that resembled the native CCL. Graft strength increased between implantation and 26 weeks after the operation, however remained weaker than controls.
Keywords: Small intestinal submucosa; cruciate ligament; xenograft; collagen graft